Potential of Moringa oleifera Leaf Extract as an Active Ingredient for Natural Hand Sanitizer - Thaal, Mario Bernardo; Pakan, Prisca Deviani; Woda, Rahel Rara (Cendana Medical Journal, 2024)
Background: COVID-19 infection has become a pandemic due to the continuously increasing number of confirmed cases worldwide, making it necessary to establish effective control and prevention measures against the spread of COVID-19. Antiseptic hand sanitizers can help prevent the transmission of infectious diseases. However, conventional hand sanitizers, which contain alcohol and synthetic chemicals, are relatively expensive and often cause skin health issues. Therefore, it is important to explore natural antiseptic alternatives as active ingredients for hand sanitizers that are more affordable, safe, effective, and accessible to all segments of society. One such medicinal plant is Moringa (Moringa oleifera), which has long been cultivated and used for traditional medicine. Objective: This study aimed to determine the potential of Moringa leaf (Moringa oleifera) extract as an active ingredient in natural hand sanitizer formulations. Methods: This study used a true experimental design with a posttest-only control group design. The treatment groups consisted of a positive control (alcohol-based hand sanitizer), a negative control (sterile aquadest), and Moringa leaf extract at concentrations of 100%, 75%, 50%, 25%, 10%, 5%, and 1%, with each group tested in triplicate against Staphylococcus aureus and Escherichia coli. Data were analyzed using One-Way ANOVA at a 95% confidence level. Results: The antibacterial activity test results showed that Moringa leaf extract has antibacterial potential against the growth of Staphylococcus aureus and Escherichia coli. The One-Way ANOVA analysis indicated a p-value of 0.000, which is lower than α = 0.05, meaning there was a significant difference in the mean diameter of the inhibition zones between the treatment groups. Conclusion: Moringa leaf (Moringa oleifera) extract has potential as an active ingredient for natural hand sanitizer formulations. Keywords : Moringa oleifera in NTT, Hand sanitizer, Antibacterial.